Test of The Effect of Workload on Performance of Desiccated Coconut - Maria Evatri Tampubolon; Lukman Adlin Harahap; Ainun Rohanah (Universitas Sumatera Utara, 2016)
Coconut plant is a plant of life, because all its parts can be utilized to meet human needs. One of the utilization is grated coconut that can be used in making bread, biscuits, sweets, taking its milk and coconut flour. This study was aimed to examine the effect of workload on the performance of grated coconut dryer. This research was conducted in May until June 2015 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, by literature study, testing equipment and parameters observation. Parameters measured were effective capacity, moisture content before and after drying, yield, power and organoleptic tests. The results showed that the workload was significantly affected the effective capacity, water content, yield, power and organoleptic tests of aroma and not significantly affected to the organoleptic test of colour and flavour. Key words: desiccated coconut, dryer, grated, workload.